Antibody responses to the surface-exposed epitopes of the trypanosome variable surface glycoprotein in N'Dama and Boran cattle - Williams, D.J.L.; Taylor, K.; Wilkie, B.; Gichuki, B.; Authié, Edith (International Laboratory for Research on Animal Diseases, 1994)
Trypanosomes are covered with a dense layer of antigenically identical glycoproteins. These molecules are highly immunogenic and elicit an antibody response in the infected host. Antibodies against the surface-exposed epitopes of the trypanosome variable surface glycoproteins (VSG) mediate the destruction and clearance of trypanosomes expressing that particular VSG. As those parasites are cleared, they are replaced by others expressing antigenically different VSG molecules. Again, an antibody response is generated. Thus trypanosome infections are characterized by waves of parasites followed by waves of VSG-specific antibody. It has been shown that trypanotolerant N'Dama cattle infected with trypanosoma congolense have significantly lower levels of parasitaemia than more susceptible Boran cattle. It has been postulated that the lower parasitaemia is the result of a more effective antibody reponse against the VSG-specific antibody responses in N'Dama and Boran cattle during an experimental T. congolense infection.